Design of a 3D Printed Helical Antenna having High Gain for 2.4 GHz ISM Band Applications - Bal, Subhradip; Mandal, Subha; Abdullha, Md. Mustafa; Sen, Gobinda (Defense science journal, 2025)
A helical antenna that is designed for circular polarisation throughout an extensive axial-ratio (AR) bandwidth is demonstrated. The antenna is constructed from copper wire and is supported by a 3D-printed polylactic Acid (PLA) structure. The antenna’s performance (reflection coefficient, axial ratio, gain, and radiation pattern) is comprehensively analysed and influenced by the geometric characteristics of the helix and the quantity of PLA used inside the coil diameter. The pre-designed PLA framework is used to construct the antenna prototype by coiling a 1 mm diameter copper wire around it. The framework is equipped with threads that are designed to support the helix of the antenna, according to the specified number of turns and distance between each turn. The antenna is suitable for a wide range of ISM band applications, as it resonates at 2.45 GHz and has a high radiation efficiency of 99 %. Additionally, it has a maximum gain of 8.01 dB. The helical antenna has a bandwidth of 0.15λ0 at the central frequency and a 3 dB axial ratio bandwidth that spans from 2.3 to 2.5 GHz. The results demonstrate the ease and feasibility of producing highly efficient helical antennas using 3D printing technology.